PRECISION VOLTAGE STABILIZERS OF POSITIVE POLARITY WITH THE LOW RESIDUAL VOLTAGE AND PROTECTING FROM ELECTROSTATIC DISCHARGE - Y. N. Kryvasheya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Results of research and design of precision voltage stabilizers of positive polarity with low value of power failure and protecting from electrostatic discharge (K1254EN3AP1) with output voltage of 1,8 V, 2,5 V, 2,85 V, 3,3 V and 5 V, given in plastic cases KT-28 (TO-220), KT-27 (TO-126, KT-89 (D-PAK) are reduced.